Genome-wide meta-analysis and replication studies in multiple ethnicities identify novel adolescent idiopathic scoliosis susceptibility loci - Khanshour, Anas M (Hum Mol Genet, 2018)
Adolescent idiopathic scoliosis (AIS) is the most common musculoskeletal disorder of childhood development. The genetic architecture of AIS is complex, and the great majority of risk factors are undiscovered. To identify new AIS susceptibility loci, we conducted the first genome-wide meta-analysis of AIS genome-wide association studies, including 7956 cases and 88 459 controls from 3 ancestral groups. Three novel loci that surpassed genome-wide significance were uncovered in intragenic regions of the CDH13 (P-value_rs4513093 = 1.7E-15), ABO (P-value_ rs687621 = 7.3E-10) and SOX6 (P-value_rs1455114 = 2.98E-08) genes. Restricting the analysis to females improved the associations at multiple loci, most notably with variants within CDH13 despite the reduction in sample size. Genome-wide gene-functional enrichment analysis identified significant perturbation of pathways involving cartilage and connective tissue development. Expression of both SOX6 and CDH13 was detected in cartilage chondrocytes and chromatin immunoprecipitation sequencing experiments in that tissue revealed multiple HeK27ac-positive peaks overlapping associated loci. Our results further define the genetic architecture of AIS and highlight the importance of vertebral cartilage development in its pathogenesis.